ANALYSIS OF A MIRNA SET (MIR-21, -181A, AND -146A) AS A METHOD OF DIFFERENTIAL DIAGNOSIS OF THYROID NODULES - R. B. Samsonov; V. S. Burdakov; T. A. Shtam; Z. A. Radzhabova; Y. V. Cheburkin; D. A. Vasilyev; E. V. Tsyrlina; S. E. Titov; M. К. Ivanov; M. V. Filatov; L. M. Berstein; N. N. Kolesnikov; et al. (Опухоли головы и шеи)
Introduction. In clinical practice, differential diagnosis of nodular thyroid diseases poses a serious problem which can be solved by development of new, safe, and specific thyroid tumor markers. Small regulatory RNAs (microRNA, miRNA) are a class of molecules that control gene expression at the post-transcriptional level. miRNAs, both intracellular and secreted into the extracellular space, can be used as markers of various diseases, including cancer. Stability of extracellular miRNAs is determined by binding to proteins and lipoproteins, or by “packing” into membrane microvesicles – exosomes. It is considered that exosomes with specific miRNA content are a result of active and biologically significant secretion, while release of other forms of miRNA is associated with apoptotic or necrotic cell death. This determines diagnostic value of exosomal fraction of circulating miRNAs, which may reflect presence or clinically significant properties of a tumor.The study objective was to explore a method of exosomal miRNA isolation, identify marker miRNAs, and estimate diagnostic value of their analysis.Methods. We used serum samples from 57 patients with nodular thyroid diseases and 13 healthy donors. Exosomes were isolated from serum by ultracentrifugation and analyzed by atomic force microscopy, laser correlation spectroscopy, and western blotting. Analysis of exosomal miRNAs was carried out by RT-PCR.Results. We have identified a specific correlation between certain miRNAs and status of thyroid nodular disease. Expression profiles of three miRNAs (miRNA-21,  miRNA-146a,  and miRNA-181a) exhibited specific characteristics for different forms of nodular thyroid disease and their analysis may have diagnostic value.Conclusions. Exosomes isolated by ultracentrifugation from serum are a source of RNA suitable for subsequent analysis of miRNA. The levels of different miRNAs in serum exosomes may differ by 1–2 times. «Marker» exosomal miRNAs have specific profiles in circulating exosomes of patients with different thyroid nodules. Clinical significance of testing exosomal miRNAs in patients with benign and malignant nodules of the thyroid gland can be increased by a parallel assessment of several molecules and analysis of the profile of their representation in exosomes. MiRNA-181a, -146a, and -21 form a diagnostic combination of «marker» molecules present in the circulating exosomes, which can be extended and used for diagnosis (differential diagnosis) of thyroid nodules.